Linking personal attributes, technical skill and managerial competence towards entrepreneurial orientation and the success of traditional home culinary industry - Shofia Amin; Husni Hasbullah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
SSurveys had shown that there are lots of people who work in the culinary business industries in Seberang Kota Jambi, and even though they were not managed professionally they had survived for quite some time. This study aimed to test the relationship between personal attributes, technical skill and managerial competence toward entrepreneurial orientation and successes. The data were collected through the questionnaire for 44 people who owned small culinary businesses in several districts in Seberang, then were analyzed using Partial Least Squares Path Modeling (PLS-SEM). The result had shown that the personal attributes and technical skills have no siginificant influence on the entrepreneurial orientation, but their managerial competence had a significant influence on their entrepreneurial orientation. Then the entrepreneurial orientation have positive influence on the success of business. So in a way, the managerial competence determine their success in business. That’s why it was needed a lot of help from the government and academicians to increase their managerial competence by giving them special guidance, counselings and trainings continuouslyKeywords: personal attributes, technical skills, managerial competence, entrepreneurial orientation, culinary home industries